Complexity perplexity: a systematic review to describe the measurement of medication regimen complexity. (November 2013) - Paquin, Allison M; Zimmerman, Kristin M; Kostas, Tia R; Pelletier, Lindsey; Hwang, Angela; Simone, Mark; Skarf, Lara M; Rudolph, James L
<x xml:space="preserve">Abstract</x> Introduction: Complex medication regimens are error prone and challenging for patients, which may impact medication adherence and safety. No universal method to assess the complexity of medication regimens (CMRx) exists. The authors aim to review literature for CMRx measurements to establish consistencies and, secondarily, describe CMRx impact on healthcare outcomes. Areas covered: A search of EMBASE and PubMed for studies analyzing at least two medications and complexity components, among those self-managing medications, was conducted. Out of 1204 abstracts, 38 studies were included in the final sample. The majority (74%) of studies used one of five validated CMRx scales; their components and scoring were compared. Expert opinion: Universal CMRx assessment is needed to identify and reduce complex regimens, and, thus, improve safety. The authors highlight commonalities among five scales to help build consensus. Common components (i.e., regimen factors) included dosing frequency, units per dose, and non-oral routes. Elements (e.g., twice daily) of these components (e.g., dosing frequency) and scoring varied. Patient-specific factors (e.g., dexterity, cognition) were not addressed, which is a shortcoming of current scales and a challenge for future scales. As CMRx has important outcomes, notably adherence and healthcare utilization, a standardized tool has potential for far-reaching clinical, research, and patient-safety impact.